PRIMARY ODONTOGENIC CYST OF THE MANDIBLE - Lepsky, V.V. (World of Medicine and Biology, 2015)
Odontogenic tumors and tumor diseases, including follicular and radicular cysts constitute about 51% of the total number of non-malignant tumors.Cyst - a tumor-like formation which is only a symptom of swelling, deformation of the body resemble the tumor and in nature tend to consist of a shell and content, often this spreading, serous, mucous, blood, etc. [12].Cysts are divided into odontogenic and neodontogennye. By odntogennym radicular cysts are follicular, retromolar (paradental) cyst.A special group of odontogenic cyst formation, the so-called primary cysts.In turn, the primary cyst related to odontogenic cysts are rare. It is a special group of tumor-like growths that do not have a direct topographic and anatomic relationship with erupted teeth, tooth germ or teething process [3, 4].Microscopic structure and some clinical and radiological features of these cysts make it possible to treat them as malformations of odontogenic epithelium. The final diagnosis can be made based on the data of histological postoperative study material [5].Treatment of primary cysts can only be surgery - a radical (cystectomy).Weather favorable after surgery, recurrence is not nablyudaetsya.Given the development of this rare disease, asymptomatic and, therefore, difficulties arise in the diagnosis and treatment of it - all of this was to study the disease.Objects and methods of research. A clinical and radiological examination and treatment of patients 47-years and patients 16 years applied to the surgical departmentof our clinic. Results of the study. The patient is 47-years complained of a fistula appeared in the mouth with a slight discharge. The patient of 16 years in the presence of swelling in the lower jaw in the 4.2, 4.1, 3.1, 3.2 teeth.From the history of the disease fistula appeared a few days ago, without any reason, painless spontaneously. Comorbidities are not noted.An objective study: the configuration of the face is not changed, the skin of normal color, the lymph nodes are not palpable. Opening the mouth free, orthognathic bite. On the eve of the oral cavity in the tooth 3.2 on the alveolar ridge has a small fistulous course with little sukrovichnym discharge, in probing his umbrella rests on the bone. Determined slight protrusion of the alveolar bone closer to the transitional fold from 4.4 to 3.4 teeth, palpation painless, dense in the center of it at 4.1 and 3.1 has a softening of the teeth, a small fluctuation. In the teeth of 4.4 and 4.7, there is a fixed prosthesis, 3.3 and 3.4 of the teeth - metal crowns.The patient is assigned a survey: blood, plain radiography of the mandible.The blood test revealed no pathology. On radiographs of the mandible is determined by the destruction of bone tissue from the tooth 4.8 to 3.8, and from the tops of the tooth roots of the teeth to the edge of the lower jaw with clear boundaries, not associated with the roots of the teeth. On the basis of clinical and radiological findings diagnosed with primary odontogenic cyst of the mandible. The patient is asked to surgery, to which he agreed.A surgical treatment under local anesthesia - plastic cystectomy. Methods of operation: made the cut on a transitional fold from 4.8 to 3.8 teeth, loose muco-periosteal flap, removed thinned the outer wall of the lower jaw, the liquid contents and cyst, the wound washed with 1% sodium dioksidina, the wound entered muco-periosteal flap, fixed in cyst cavity yodoformnym swab. When dressing a tampon is changed every 4-5 days. On the appearance of epithelialization in the cyst cavity the patient was discharged. Weather favorable. Histological examination revealed the presence of epithelial cells, red blood cells.The patient 16 years lymph nodes are not palpable. Opening the mouth free, bite ortagnatichesky. On the eve of the oral cavity is defined by protrusion of the alveolar process of the lower jaw, covered with intact mucosa. Palpable: painless swelling, firm, located in the 4.2, 4.1, 3.1, 3.2 teeth, teeth intact, percussion and temperature stimuli did not react. On sighting the radiograph of the alveolar process of the lower jaw bone destruction was defined with clear boundaries from 4.2 to 3.2 tooth width of up to 1 cm. The roots of the teeth were projected on education, and only a CT scan showed that the cystic cavity is located in front of the roots of teeth. Treatment of patients were surgically: tsisektomiya. Given the small size of the tumor, the wound sewn up tight. The postoperative period was uneventful, wound healing by first intention, was discharged on recoveryThe paper presents a rare case of primary odontogenic cysts large size (from 4.8 to 3.8 teeth) on the lower jaw, flowing bezsimptomno and discovered by accident. A surgery for cyst removal - plastic cystectomy. Weather favorable.
Keywords: first brush; diagnosis; method of treatment